2012
DOI: 10.3354/meps09778
|View full text |Cite
|
Sign up to set email alerts
|

Migratory patterns in hawksbill turtles described by satellite tracking

Abstract: The advent of telemetry has improved knowledge of the spatio-temporal distribution of marine species of conservation concern. Among the sea turtles, the movements of the hawksbill turtle Eretmochelys imbricata are among the least well described. We tracked 10 adult female hawksbill turtles by satellite after nesting in the Dominican Republic (DR) and describe a dichotomy in patterns of movement: some (n = 2) turtles remained in the DR, while others migrated to waters off Honduras and Nicaragua (n = 5) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 55 publications
3
30
0
Order By: Relevance
“…Here we analyse tracking data from DR nesting hawksbills (building on findings in Hawkes et al 2012) with respect to (1) behaviour of hawksbill females during the period from the date of attachment at nesting until the final nesting event before departure from the breeding grounds and (2) an assessment of the level of protection afforded to these turtles in their breeding and foraging areas.…”
Section: Introductionmentioning
confidence: 99%
“…Here we analyse tracking data from DR nesting hawksbills (building on findings in Hawkes et al 2012) with respect to (1) behaviour of hawksbill females during the period from the date of attachment at nesting until the final nesting event before departure from the breeding grounds and (2) an assessment of the level of protection afforded to these turtles in their breeding and foraging areas.…”
Section: Introductionmentioning
confidence: 99%
“…Red lines show tracks on departure during the nesting season. Figure (C) shows the migrations of ten satellite tracked adult female hawksbill turtles [102]. White crosses show deployment locations for satellite tracked turtles in Jaragua and Saona Island.…”
Section: Resultsmentioning
confidence: 99%
“…Satellite tracking studies of the postnesting migration towards Brazil (Figure 3; [63,64]) indeed revealed signi�cant navigational feats during the oceanic crossing, such as the presence of long straight segments and the ability to orient towards the individually speci�c feeding areas from far away [63], although not always following the most direct path ( Figure 3). Similar goal-oriented postnesting migrations involving oceanic crossings are known in other green turtle populations (e.g., in Galapagos, Hawaii, or Polynesian islands, [102,103,105]), as well as in other species [92,97,[109][110][111]. Juveniles too are able to undertake long-distance oceanic migrations and one of the longest journey tracked in a sea turtle actually belongs to a juvenile loggerhead that crossed the entire Paci�c ocean covering over 11,000 km in about 11 months while moving from California towards its Japanese natal area [88].…”
Section: Seamentioning
confidence: 99%